LIPOPROTEIN-ASSOCIATED PHOSPHOLIPASE A2 (Lp‐PLA2) AS A PREDICTOR OF END-STAGE RENAL DISEASE IN PATIENTS WITH DIABETIC NEPHROPATHY - Kostovska, Irena; Cekovska, Svetlana; Tosheska Trajkovska, Katerina; Labudovikj, Danica; Brezovska Kavrakova, Julijana; Topuzovska, Sonja; Emin, Melda; Ampova Hristina; Stanojevska, Elena; Nedeska Minova, Natasha (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a specific biomarker for vascular inflammation. It is associated with microvascular complications such as diabetic nephropathy (DN) in patients with type 2 diabetes mellitus. To determine the predictive value of Lp-PLA2 concentration/activity for end-stage renal disease (ESRD) in patients with DN. A total of 94 patients included in this cross-sectional study with DN were divided into four stages of chronic kidney disease (CKD) according to CKD-EPI: Stage II (n=20), Stage IIIa (n=29), Stage IIIb (n=38), and Stage IV (n=7). Forty-four healthy subjects were used as a control group. In addition to anamnestic data (age, gender, body weight, height, glycemic control), we measured the concentration of glucose, total cholesterol, triacylglycerols, blood urea, and creatinine in the blood serum using standard photometric methods. Lp-PLA2 concentration/activity was measured by chemiluminescence immunoassay-CLIA. Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) serum creatinine was used to determine the GFR and CKD stages. We found significant differences among subgroups of patients with DN divided according to CKD stage and healthy subjects regarding age, body mass index, duration of disease, blood glucose, glycated hemoglobin, total cholesterol, triacylglycerols, blood urea, serum creatinine, GFR, and Lp-PLA2. A significant negative correlation was found between Lp‐PLA2 and GFR. ROC analysis showed that Lp-PLA2 had a positive predictive value of 98.3% in patients with DN. Lp-PLA2 gradually increased in stages of DN. Lp-PLA2 could be considered as a potential predictive biomarker for the progression of DN to ESRD.
Keywords: lipoprotein-associated phospholipase A2 (Lp-PLA2); end-stage renal disease; diabetic nephropathy